2001
DOI: 10.1111/1467-8624.00318
|View full text |Cite
|
Sign up to set email alerts
|

Children's Understanding of Emotion in Speech

Abstract: Children's understanding of emotion in speech was explored in three experiments. In Experiment 1, 4- to 10-year-old children and adults (N = 165) judged the happiness or sadness of the speaker from cues conveyed by propositional content and affective paralanguage. When the cues conflicted (i.e., a happy situation was described with sad paralanguage), children relied primarily on content, in contrast to adults, who relied on paralanguage. There were gradual developmental changes from 4-year-olds' almost exclusi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

31
227
5
4

Year Published

2001
2001
2022
2022

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 207 publications
(274 citation statements)
references
References 53 publications
31
227
5
4
Order By: Relevance
“…These data are consistent with reports of extensive variability in social referencing in the second year of life (Blackford & Walden 1998, Walden 1991, and parallel a similar transition in expression around the time of first words (Bloom 1993, Bloom et al 1988. Finally, these data complement research with 4-to 7-year-olds in whom a tendency toward greater weighting of linguistic, relative to paralinguistic, meaning has been reported (Friend 2000, Friend & Bryant 2000, Morton & Trehub 2001 and suggest that this bias emerges out of the process of language acquisition. …”
Section: Discussionsupporting
confidence: 87%
“…These data are consistent with reports of extensive variability in social referencing in the second year of life (Blackford & Walden 1998, Walden 1991, and parallel a similar transition in expression around the time of first words (Bloom 1993, Bloom et al 1988. Finally, these data complement research with 4-to 7-year-olds in whom a tendency toward greater weighting of linguistic, relative to paralinguistic, meaning has been reported (Friend 2000, Friend & Bryant 2000, Morton & Trehub 2001 and suggest that this bias emerges out of the process of language acquisition. …”
Section: Discussionsupporting
confidence: 87%
“…Previous studies have shown that the ability to answer questions that demand complex contextual processing, such as understanding implicit meanings, develops with age (Loukusa et al, 2007;Loukusa, Ryder, & Leinonen, 2008;. At around eight years of age children begin to pay greater attention to all of the available relevant cues, including paralinguistic aspects of communication, and they no longer focus substantially on propositional content (Bosco, Angeleri, Colle, Sacco, & Bara, 2013;Morton & Trehub, 2001). An earlier study by Loukusa et al (2007) showed that at the age of seven children can connect different kinds of contextual information in order to infer the implicit meaning of an utterance.…”
Section: Development Of Social-pragmatic Comprehensionmentioning
confidence: 99%
“…Burnham et al, 2002;Uther et al, 2007) into IDS, and other investigations into children's vocal emotional understanding (e.g. Morton & Trehub, 2001), have utilized different filters.…”
Section: Introductionmentioning
confidence: 99%